Boranes in Organic Chemistry - Brown, Herbert C. (Cornell University Press, 2019)
The leading researcher in the uses of boranes in organic synthesis here reviews his work over the past thirty-five years, covering such areas as steric strains, the nonclassical ion problem, selective reductions, hydroboration, and the organoboranes as synthetic intermediates. But more than an exposition of enormous accomplishment, the book is a scientific autobiography that will provide chemists with historical perspective on their profession. The author's detailed narrative of his own research experiences not only adds to the understanding of the present state of the study of boranes, but will serve as a stimulus to imaginative research in the future.